Urban Energy Scenario of Household Sector in Bhaktapur Municipality for Sustainable Energy Development - K.C., Raj Kumar; Nakarmi, Amrit Man (Journal of Advanced College of Engineering and Management, 2021)
This study aims to analyse energy scenarios of Bhaktapur Municipality through primary data survey of 165 houses as a function of household's characteristics. Three scenarios are considered business-as-usual (BAU), Sustainable Energy scenario (SED) and Accelerated Growth Scenario (AGS). BAU, SED and AGS show an expected energy growth at annual rates of4.08%, 3.71% and 4.01%; with economic growth of 4.6%, 7.0% and 9.2% respectively. Whereas, the electricity consumption per household in the SEDand AGS are 3,840KWh and 4,698KWh respectively, lies in tier-5 as per SDG. Fuel imported cost NRs. 471 million and NRs. 523 million can be saved in SED and AGS Scenarios respectively as compare to BAU scenario. Overall, under all three scenarios, it was found that total GHG emission in 2018 was 7.59 kilotons to nil in 2030 for SED and AGS.Furthermore,NPV value in AGS and SED scenarios are in negative value which means both scenarios is economically viable.